Characterization of G-Quadruplex Motifs in espB, espK, and cyp51 Genes of Mycobacterium tuberculosis as Potential Drug Targets - Mishra, Subodh Kumar; Shankar, Uma; Jain, Neha; Sikri, Kriti; Tyagi, Jaya Sivaswami; Sharma, Tarun Kumar; Mergny, Jean-Louis; Kumar, Amit (Molecular therapy. Nucleic acids, 2019)
G-quadruplex structure forming motifs are among the most studied evolutionarily conserved drug targets that are present throughout the genome of different organisms and susceptible to influencing various biological processes. Here we report highly conserved potential G-quadruplex motifs (PGQs) in three essential genes (espK, espB, and cyp51) among 160 strains of the Mycobacterium tuberculosis genome. Products of these genes are involved in pathways that are responsible for virulence determination of bacteria inside the host cell and its survival by maintaining membrane fluidity. The espK and espB genes are essential players that prevent the formation of mature phagolysosome and antigen presentation by host macrophages. The cyp51 is another PGQ-possessing gene involved in sterol biosynthesis pathway and membrane formation. In the present study, we revealed the formation of stable intramolecular parallel G-quadruplex structures by Mycobacterium PGQs using a combination of techniques (NMR, circular dichroism [CD], and gel electrophoresis). Next, isothermal titration calorimetry (ITC) and CD melting analysis demonstrated that a well-known G-quadruplex ligand, TMPyP4, binds to and stabilizes these PGQ motifs. Finally, polymerase inhibition and qRT-PCR assays highlight the biological relevance of PGQ-possessing genes in this pathogen and demonstrate that G-quadruplexes are potential drug targets for the development of effective anti-tuberculosis therapeutics.